Ping-pong diplomacy : the secret history behind the game that changed the world - Griffin, Nicholas, 1971- (New York : Scribner, 2014)
Examines how an aristocratic British spy circumvented more than 20 years of antagonistic foreign policy between China and the United States to further a fateful Communist agenda during the World Table Tennis Championships, revealing how players were tortured and murdered throughout the Cultural Revolution.
The West. Not-so-humble beginnings ; Gentlemanly rebel ; Roast beef and Russia ; The dangers of derision ; Table tennis and Trotsky ; Culture and the coming war ; Suspect ; Brothers ; The end of the game? ; The Jewish question -- The East. Table tennis bandits ; The Trojan dove ; The rise of Asia ; Tiny tornadoes ; Reconnaissance ; The golden game ; Setting the table ; The end of brotherhood ; Preparation ; Sacrifice ; Nourishing the team ; Ping-pong espionage ; Cheery martial music ; The chance to shine ; Fallout ; Heroes of the nation ; Spreading the gospel ; The grinding halt ; Under pressure ; House of cards ; Death to the doubters ; Down to the country -- East meets West. The world at war ; The seeds of peace ; Long hair, light heart ; Could the Great Wall crumble? ; A measured coincidence ; An invitation home ; Surprise ; Decisions to be made ; The worries ; Crossing the borders ; All eyes on America ; Tension ; Nixon's game ; Political ping-pong -- Aftermath. Return game ; Capital performance ; United Nations ; The hippie opportunist ; The heights ; The costs.
Includes bibliographical references (pages 281-323) and index.
Keywords: Table tennis; China -- Foreign relations -- United States; United States -- Foreign relations -- China; Diplomatic relations; Table tennis; China; United States; Table tennis; China -- Foreign relations -- United States; United States -- Foreign relations -- China